5p-12-3(p+8)=4

Simple and best practice solution for 5p-12-3(p+8)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p-12-3(p+8)=4 equation:


Simplifying
5p + -12 + -3(p + 8) = 4

Reorder the terms:
5p + -12 + -3(8 + p) = 4
5p + -12 + (8 * -3 + p * -3) = 4
5p + -12 + (-24 + -3p) = 4

Reorder the terms:
-12 + -24 + 5p + -3p = 4

Combine like terms: -12 + -24 = -36
-36 + 5p + -3p = 4

Combine like terms: 5p + -3p = 2p
-36 + 2p = 4

Solving
-36 + 2p = 4

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 2p = 4 + 36

Combine like terms: -36 + 36 = 0
0 + 2p = 4 + 36
2p = 4 + 36

Combine like terms: 4 + 36 = 40
2p = 40

Divide each side by '2'.
p = 20

Simplifying
p = 20

See similar equations:

| f(-3)=-2(3x-2)+x+9 | | 3-7(-2)-8= | | -7w=42 | | 15x+x=192 | | 20x^3+31x^2+12x=0 | | 5x-3(2x+8)=7 | | 10x+10=6x+26 | | -5r-2r=-14 | | x^2+2c-a=0 | | 6k-30=10k | | 9x+3=-4+5x+19 | | 2m+1/9=12-7m/6 | | -2(3x-2)+x+9= | | 4+5h=39 | | f(x)=(4x-5)(3x^3-x^2+1) | | 4x-8=6(x+4)+2x | | 8(x+4)+2=34 | | 5y+2y=28 | | 10x+16=6x+26 | | A/9.06=8.2 | | 4x-2(x-5)=-3+4x-1 | | 7p=-20 | | 5x+16=6x+9 | | 2(6-7x)=-6-8x | | 18-3x+7=-46 | | 15-(8x+5)=6 | | 8+32n=31n+27 | | 1/2x-1=15 | | 1/2x-1=15 | | 34a-2=2a+32 | | -3r-3r=-5r+3 | | 32r^2=20r+63 |

Equations solver categories